2006
DOI: 10.4049/jimmunol.176.4.2568
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Tolerance Is Induced Selectively in Thoracic Lymph Nodes but Executed Pervasively at Distant Mucosal and Nonmucosal Tissues

Abstract: Under immunogenic conditions, both the site of initial Ag exposure and consequent T cell priming in specific draining lymph nodes (LNs) imprint the ensuing immune response with lasting tissue-selective tropism. With respect to immune tolerance, whether the site of tolerance induction leads to compartmentalized or, alternatively, pervasive tolerance has not been formally investigated. Using a murine model of inhalation tolerance, we investigated whether the induction of respiratory mucosal tolerance precludes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 78 publications
2
8
0
Order By: Relevance
“…B cells have also been shown to regulate the Ag presenting function and maturation of dendritic cells (16), and the possibility of B cells from LIT HLN influencing Ag presentation during the course of our model remains to be investigated. The concept of B cells in regional LIT HLNs contributing to the regulation of AAD is consistent with the recent description that such local regulatory networks exist in draining lymph nodes and regulate inflammatory responses at adjacent mucosal sites (41). Similarly, the development of tolerance to intranasal administration of Ag is dependent on B cells in regional lymphoid tissue (42).…”
Section: Discussionsupporting
confidence: 60%
“…B cells have also been shown to regulate the Ag presenting function and maturation of dendritic cells (16), and the possibility of B cells from LIT HLN influencing Ag presentation during the course of our model remains to be investigated. The concept of B cells in regional LIT HLNs contributing to the regulation of AAD is consistent with the recent description that such local regulatory networks exist in draining lymph nodes and regulate inflammatory responses at adjacent mucosal sites (41). Similarly, the development of tolerance to intranasal administration of Ag is dependent on B cells in regional lymphoid tissue (42).…”
Section: Discussionsupporting
confidence: 60%
“…A total of 1.25 3 10 3 washed BMDC were then added together with 1 3 10 5 purified CD4 + OVA-TCR transgenic T cells for 48 h, pulsed with [ T cell hyporesponsiveness in DLN and the airway mucosa that is mediated by a marked downregulation of allergen capture by AMDC subsets. These data are consistent with our and other studies showing induction of physiological and immunological tolerance after repeated exposure to innocuous allergens (11,13,16,38) and with a previous report that this process is dependent on the CCR7-guided migration of allergen-bearing DC to the DLN (18). We observed that inhaled aeroallergen is effectively captured by both CD11b hi and CD11b lo subsets of AMDC, equating to the CD103 2 and CD103 + DC subsets that have recently been described in both the lung and gut (3).…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, previous studies have demonstrated that short-term or continuous intranasal exposure of mite allergen, but not of OVA, caused eosinophilia in BAL fluid and bronchoconstriction in BALB/c mice, along with elevated Th2-cell-associated production of antibodies in serum and Th2-cell-associated production of cytokines by splenocytes (28,49), whereas other studies have demonstrated that repeated exposure of BALB/c mice to an inhaled low dose of OVA inhibited the potential to develop a specific Th2 response in the periphery due to a noncompartmentalized induced immune tolerance (5,44). In a recent study, the prevention of a cellular and a humoral Th2-mediated allergic response was obtained by intranasal administration of three consecutive high doses of OVA (100 g), whereas lower doses (10 g) were found to be less effective and intranasal treatment was less effective than orally induced tolerance (29).…”
Section: Discussionmentioning
confidence: 86%